Non‐typeable Haemophilus influenzae purulent pericarditis in a child with cystic fibrosis. Issue 7 (4th February 2016) - Downes, Kevin J; Abulebda, Kamal; Siracusa, Christopher; Moore, Ryan; Staat, Mary A; Poynter, Sue E
Abstract: Early airway colonization and infection with Haemophilus influenzae in children with cystic fibrosis (CF) is common. Although the pathogenicity of non‐typeable H. influenzae (NTHi) in patients with CF is controversial, this organism can cause both upper and lower respiratory tract infections. Extra‐pulmonary disease, however, is rare. Purulent pericarditis is a suppurative complication of bacterial infection of the pericardial space that can arise as a result of direct extension from an adjacent infection. We describe a case of purulent pericarditis due to NTHi in a young child with CF that developed as a complication of inadequately treated bronchopneumonia.